Social Network Analysis: E-Marketing Sales of “Kue Lebaran” in the Perspective of the Technology Acceptance Model - Sitti Hardiyanti Arhas; Risma Niswaty; Tri Cahyono; Nawir Rahman (Universitas Negeri Makassar, 2022)
E-marketing creates fundamental changes in business and consumer behavior, this happens because marketing does not require a lot of money, in contrast to traditional marketing. The purpose of this study was to determine e-marketing in selling Eid cakes (kue lebaran) from the perspective of the Technology Acceptance Model by using Social Network Analysis. The data is obtained from tweets on the Twitter application, the data obtained are tweets from April 2-20 2022. Data analysis uses the ATLAS.ti application. This study uses the keyword